2010
DOI: 10.1128/cvi.00189-10
|View full text |Cite
|
Sign up to set email alerts
|

Monofunctional and Polyfunctional CD8+T Cell Responses to Human Herpesvirus 8 Lytic and Latency Proteins

Abstract: Human herpesvirus 8 (HHV-8) is the etiological agent of Kaposi's sarcoma, primary effusion lymphoma, and multicentric Castleman's disease. It is postulated that CD8؉ T cell responses play an important role in controlling HHV-8 infection and preventing development of disease. In this study, we investigated monofunctional and polyfunctional CD8 ؉ T cell responses to HHV-8 lytic proteins gB (glycoprotein B) and K8.1 and latency proteins LANA-1 (latency-associated nuclear antigen-1) and K12. On the basis of our pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 44 publications
0
39
0
Order By: Relevance
“…T-cell responses to KSHV-encoded latent antigens and lytic antigens have been identified in both healthy immunocompetent donors and immunocompromised patients (32)(33)(34)(35)(36)(37). Although generally weak, KSHV-specific CD8 T cells responses are more frequent, diverse, and strong in asymptomatic KSHV-infected patients than Kaposi's sarcoma patients (38).…”
Section: Discussionmentioning
confidence: 98%
“…T-cell responses to KSHV-encoded latent antigens and lytic antigens have been identified in both healthy immunocompetent donors and immunocompromised patients (32)(33)(34)(35)(36)(37). Although generally weak, KSHV-specific CD8 T cells responses are more frequent, diverse, and strong in asymptomatic KSHV-infected patients than Kaposi's sarcoma patients (38).…”
Section: Discussionmentioning
confidence: 98%
“…Hence, a disruption of the RFX complex by LANA may result in a reduced binding of NLRC5 to the MHC-I enhanceosome, thus leading to reduced expression of MHC-I genes as well. MHC-I antigen presentation is critical for the activation of CD8 ϩ T cells, which has also been shown to play an important role in controlling KSHV infections (75,76). The role of LANA in inhibiting MHC-I through this mechanism remains to be explored, but targeting of the RFX complex by KSHV appears to help the virus dodge both MHC-I and MHC-II antigen-presenting pathways and consequently evade CD4 ϩ T and CD8 ϩ T cell immunities simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…9 Furthermore, ex vivo stimulation of PBMCs with dendritic cells sensitized with overlapping LANA peptides has been shown to stimulate CD8 ϩ T-cell responses. 5 Using these LANA-specific CD4 ϩ clones to probe recognition of LANA-expressing cells, we found that EBV-transformed B cells, cells that have an intact class II antigen processing pathway, could efficiently process and present LANA antigens. However, when the clones were tested against most PELs, cells that natively express LANA, no recognition was seen, nor when the protein was overexpressed or fed to the PELs.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively low T-cell responses to LANA and Kaposin have been described in healthy immunocompetent donors; 5,6 however, most studies have been undertaken using donors with a disrupted immune system or in disease settings, focusing on responses to LANA and Kaposin. Thus, HIV-infected patients on HAART who control KSHV have been found to make T-cell responses to LANA, MCD patients make responses comparable to HIV patients on HAART, but patients with KS disease have very weak or no detectable responses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation